PERENCANAAN DAN PENGAWASAN PEMBANGUNAN DESA TENTANG PELAYANAN KESEHATAN - Befi Sucining Sari (Kybernan: Jurnal Studi Kepemerintahan, 2021)
This study discusses how the planning and supervision of village development regarding health services requires good planning in development, besides that the village government is also required to be more accountable and participatory in carrying out the mandate to develop villages to be more advanced. to determine the quality of the success of village development. It can be seen from the role of the community in providing aspirations, ideas, supervising the performance of village officials, and carrying out assigned tasks. So that people can easily get information and data related to village development, especially in the field of rural health services. The method used is Literature Review reading and reviewing themes related to planning and monitoring village development regarding health services. By using the literature review method, it is possible to assess the shortcomings of previous researchers so that they can make improvements, a more regular formulation. Thus, a journal review is a text that contains a summary of scientific research on a particular topic. In the process of planning and supervising village development, health services must provide good services according to the needs of the community and according to existing standards. The limitation of this research is that the data obtained is not too much because there are several journals that I can not review, besides that the examples of the articles presented are different from the conditions that exist in each country so that there needs to be a critical understanding of the government system in the example articles. Articles that are used as references, besides that, special considerations need to be made in determining similarities and new discoveries from articles that are used as reference materials to develop the main idea according to the chosen topic and title.